Development Of Student Worksheets Based On Local Potential Integrated Islamic Values To Improve The Critical Thinking Of Madrasah Tsanawiyah Students - Ade Haerullah; Ningsi Saibi; Magfirah Rasyid; Abbas Kasra; Jassia Pagala (Biopedagogia, 2023)
Science (Natural Science) learning based on local potential integrated with Islamic values provides new experiences to madrasah students that natural science and Islamic religious teachings are closely related and cannot be separated from each other. Learning like this can train students to think holistically from various points of view and think more deeply so that students' critical thinking abilities can develop. The integration of Islamic values in science learning opens the view for students in Madrasa that the source of science learning is not only natural phenomena and advances in science and technology. This research is a type of development research. The stages of LKPD development are carried out in 4 (four) stages, referring to the Thiagarajan 4-D Model. The results of the learning device development show that the average value is 96.27% so it is declared very very feasible. Furthermore, the LKPD which has been declared very suitable can be tested on a limited scale on 29 class VII students at MTs SC Ternate. The results of the limited scale trial show that there is an influence of the use of LKPD based on local potential integrated with Islamic values on critical thinking skills with a significance level of 0.003, because the sig value is 0.05, the alternative hypothesis is accepted. The results of this hypothesis test can be concluded that the use of LKPD influences students' critical thinking abilities and is effectively applied to learning.